Hiszpańska wojna domowa – nowe spojrzenie na pierwsze starcie totalitaryzmów i propagandę zwaśnionych obozów - Sajna-Kunowsky, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The reviewed book by the British historian Antony Beevor (born in 1946) is a comprehensive work on the Spanish Civil War (1936-1939). It adds new details to the rich literature of the subject, paying particular attention to, among others, the intervention of the totalitarian regimes of Europe at that time, i.e. German Nazis, Italian fascists and Soviet communists. An important aspect discussed in the book is the propaganda (internal and external) used by both warring camps. The monograph is neutral — in some fragments one can even notice “symmetrical” treatment of both sides of the conflict, e.g. in the case of atrocities committed. This review article also cites other sources from the extensive literature on the subject.
Keywords: authoritarianism; fascism; Franco, Francisco (1892-1975); Spain; communism; nazism; propaganda; totalitarianisms; civil war